Viral microRNA effects on pathogenesis of polyomavirus SV40 infections in syrian golden hamsters. - Shaojie Zhang (Public Library of Science (PLoS), 2014)
Effects of polyomavirus SV40 microRNA on pathogenesis of viral infections in vivo are not known. Syrian golden hamsters are the small animal model for studies of SV40. We report here effects of SV40 microRNA and influence of the structure of the regulatory region on dynamics of SV40 DNA levels in vivo. Outbred young adult hamsters were inoculated by the intracardiac route with 1×10⁷ plaque-forming units of four different variants of SV40. Infected animals were sacrificed from 3 to 270 days postinfection and viral DNA loads in different tissues determined by quantitative real-time polymerase chain reaction assays. All SV40 strains displayed frequent establishment of persistent infections and slow viral clearance. SV40 had a broad tissue tropism, with infected tissues including liver, kidney, spleen, lung, and brain. Liver and kidney contained higher viral DNA loads than other tissues; kidneys were the preferred site for long-term persistent infection although detectable virus was also retained in livers. Expression of SV40 microRNA was demonstrated in wild-type SV40-infected tissues. MicroRNA-negative mutant viruses consistently produced higher viral DNA loads than wild-type SV40 in both liver and kidney. Viruses with complex regulatory regions displayed modestly higher viral DNA loads in the kidney than those with simple regulatory regions. Early viral transcripts were detected at higher levels than late transcripts in liver and kidney. Infectious virus was detected infrequently. There was limited evidence of increased clearance of microRNA-deficient viruses. Wild-type and microRNA-negative mutants of SV40 showed similar rates of transformation of mouse cells in vitro and tumor induction in weanling hamsters in vivo. This report identified broad tissue tropism for SV40 in vivo in hamsters and provides the first evidence of expression and function of SV40 microRNA in vivo. Viral microRNA dampened viral DNA levels in tissues infected by SV40 strains with simple or complex regulatory regions.